ANALISIS NILAI-NILAI MORAL DALAM NOVEL CATATAN CINTA ISTRI KARYA SARI MEUTIA - Dwi Warry Octaviana (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2022)
In a literary work, of course, it has a good value in the form of writing that is delivered in a communicative and distinctive style about the author's intent for aesthetic purposes. So, many people say that literature is a reflection of life. Therefore, literary works are created by writers to be enjoyed, understood, and utilized by the community in life. The researcher chose the novel of Catatan Cinta Istri because the novel has many elements of moral values. Therefore, this study was aimed at finding out the moral values ??contained in the novel of Catatan Cinta Istri. This research employed a qualitative descriptive study. This study used an objective literary approach, which means an approach that focuses on literary works as a whole. The subject was the novel of Catatan Cinta Istri by Sari Meutia. The study focused on moral values. The study revealed some results. The results showed that there were 60 moral values ??with the aspects of human relations with oneself, 44 moral values ??with the aspects of human relations with other humans in the social or natural environment. And 45 moral values ??with the aspects of human relations with God. The most moral values ??found in the novel of Catatan Cinta Istri by Sari Meutia were in the aspects of human relations with oneself. Keywords: Analysis, Moral Values, Novel.